Wnt signaling pathway activities may be altered in primary Sjogren's syndrome - Karatas, Ahmet; Omercikoglu, Zuhal; Oz, Burak; Dagli, Adile Ferda; Catak, Onur; Erman, Fazilet; Koca, Suleyman Serdar (Tubitak Scientific & Technological Research Council Turkey, 2021)
Background/aim: Sjogren's syndrome (SS) is an autoimmune disease and its pathogenesis is still not completely clear. The wingless (Wnt)/beta-catenin pathway has recently been shown to play an important role in inflammation. This study aims to determine the serum and saliva levels of Dickkopf (DKK)1 and sclerostin and to evaluate Wnt-1 and Wnt-3a expression in the salivary gland in patients with primary SS. Materials and methods: This study included 30 patients diagnosed with SS, 30 patients diagnosed with systemic lupus erythematosus (SLE), and 29 healthy controls. Serum and saliva levels of DKK1 and sclerostin were measured and the expressions of Wnt1 and Wnt3a in the salivary gland were measured immunohistochemically. Results: Serum DKK1 and sclerostin levels were lower in the SS and SLE groups compared to the control group (both p < 0.001). Saliva DKK1 levels were higher in the SS group compared to the control and SLE groups (p = 0.004 and p = 0.009, respectively). Wnt1 and Wnt3a expression were found in salivary gland tissue samples in 71.4% of primary SS patients and relatively frequent than control group. Conclusions: Serum DKK1 and sclerostin levels in primary SS and SLE were decreased. Moreover, levels of Wnt1 and Wnt3a expression in the salivary gland were also elevated in primary SS. Therefore, it can be concluded that the Wnt/beta-catenin pathway activities may be altered in case of glandular inflammation.
Keywords: Sjogren syndrome; wingless; sclerostin; dickkopf-1